A White Matter Connection of Schizophrenia and Alzheimer's Disease. (18th July 2020) - Kochunov, Peter; Zavaliangos-Petropulu, Artemis; Jahanshad, Neda; Thompson, Paul M; Ryan, Meghann C; Chiappelli, Joshua; Chen, Shuo; Du, Xiaoming; Hatch, Kathryn; Adhikari, Bhim; Sampath, Hemalatha; Hare, Stephanie; et al.
Abstract: Schizophrenia (SZ) is a severe psychiatric illness associated with an elevated risk for developing Alzheimer's disease (AD). Both SZ and AD have white matter abnormalities and cognitive deficits as core disease features. We hypothesized that aging in SZ patients may be associated with the development of cerebral white matter deficit patterns similar to those observed in AD. We identified and replicated aging-related increases in the similarity between white matter deficit patterns in patients with SZ and AD. The white matter "regional vulnerability index" (RVI) for AD was significantly higher in SZ patients compared with healthy controls in both the independent discovery (Cohen's d = 0.44, P = 1·10 –5, N = 173 patients/230 control) and replication (Cohen's d = 0.78, P = 9·10 –7, N = 122 patients/64 controls) samples. The degree of overlap with the AD deficit pattern was significantly correlated with age in patients ( r = .21 and .29, P < .01 in discovery and replication cohorts, respectively) but not in controls. Elevated RVI-AD was significantly associated with cognitive measures in both SZ and AD. Disease and cognitive specificities were also tested in patients with mild cognitive impairment and showed intermediate overlap. SZ and AD have diverse etiologies and clinical courses; our findings suggest that white matter deficits may represent a key intersecting point for these 2 otherwise distinct diseases. Identifying mechanisms underlying this white matter deficit pattern may yield preventative and treatment targets for cognitive deficits in both SZ and AD patients.